Multimodular Assessment of a Traumatic Bone Cyst Overlapped with Apical Periodontitis - Davide Musu; Giulia Bardini; Hagay Shemesh; Claudia Dettori; Elisabetta Cotti (Hindawi Limited, 2020)
Traumatic bone cyst (TBC), a "pseudocyst" that usually affects long bones, is a rare lesion among cystic lesions in the jaws. The most commonly affected site is the posterior mandible. Most of the time, TBC is asymptomatic and discovered during routine radiographic examination. The treatment recommended for TBC is surgical exploration followed by curettage of the bony walls, which also serves as a diagnostic procedure. A 27-year-old Caucasian male with a noncontributory medical history was referred to our department for the endodontic evaluation of the mandibular right first and second molars, which were connected to an extensive asymptomatic osteolytic lesion. A multimodular diagnostic assessment involving CBCT imaging, ultrasound, and histopathologic examination led to a definite diagnosis of a TBC overlapping with apical periodontitis (AP). Subsequently, a multidisciplinary treatment approach was performed, including surgical excision and biopsy of the lesion, endodontic retreatment of the right mandibular first molar, and postsurgical root canal treatment of the second molar. During the follow-up period of five years, the patient was reassessed periodically once a year and showed, in the absence of signs and symptoms, progressive healing of the affected area. The present article reports a case following the CARE guidelines of a TBC combined with AP where a multimodular diagnostic assessment was performed and discusses the possible pathogenetic mechanisms involved in its generation.